X-ray Structure and Magnetic Properties of Heterobimetallic Chains Based on the Use of an Octacyanidodicobalt(III) Complex as Metalloligand - Maria-Gabriela Alexandru; Diana Visinescu; Sergiu Shova; Abdeslem Bentama; Francesc Lloret; Joan Cano; Miguel Julve (Magnetochemistry, 2020)
The assembly of [Co2III(μ-2,5-dpp)(CN)8]2− anions and [MII(CH3OH)2(DMSO)2]2+ cations resulted into the formation of two heterobimetallic 1D coordination polymers of formula [MII(CH3OH)2(DMSO)2(μ-NC)2Co2III(μ-2,5-dpp)(CN)6]n·4nCH3OH [M = CoII (1)/FeII (2) and 2,5-dpp = 2,5-bis(2-pyridyl)pyrazine. The [Co2III(μ-2,5-dpp)(CN)8]2− metalloligand coordinates the paramagnetic [MII(CH3OH)2(DMSO)2]2+ complex cations, in a bis-monodentate fashion, to give rise to neutral heterobimetallic chains. Cryomagnetic dc (1.9–300 K) and ac (2.0–13 K) magnetic measurements for 1 and 2 show the presence of Co(II)HS (1) and Fe(II)HS (2) ions (HS – high-spin), respectively, with D values of +53.7(5) (1) and −5.1(3) cm−1 (2) and slow magnetic relaxation for 1, this compound being a new example of SIM with transversal magnetic anisotropy. Low-temperature Q-band EPR study of 1 confirms that D value is positive, which reveals the occurrence of a strong asymmetry in the g-tensors and allows a rough estimation of the E/D ratio, whereas 2 is EPR silent. Theoretical calculations by CASSCF/NEVPT2 on 1 and 2 support the results from magnetometry and EPR. The analysis of the ac magnetic measurements of 1 shows that the relaxation of M takes place in the ground state under external magnetic dc fields through dominant Raman and direct spin-phonon processes.